Compensating Pixel Circuit Driving AMOLED Display With a-IGZO TFTs - Lin, Chih-Lung; Chang, Wen-Yen; Hung, Chia-Che (IEEE electron device letters, 2013)
This letter presents a novel active-matrix organic light-emitting diode (AMOLED) pixel circuit that uses amorphous indium-gallium-zinc oxide (a-IGZO) thin-film transistors (TFTs) with a bottom-gate structure to compensate for the threshold voltage shift of the TFT. An a-IGZO TFT driven AMOLED display (70 × 70 pixels) on a glass substrate is fabricated and its reliability is evaluated under electrical stress.